Chylous ascites in cirrhosis-A case report - Laudari, S; Subedi, K; Toyena, R; Vamja, J; Kumar, S Nanda; Subedi, S (Journal of College of Medical Sciences-Nepal, 2012)
Chylous ascites is a rare presentation in cirrhotic liver disease but its incidence has increased because of aggressive cardiothoracic/abdominal surgeries and increasing survival of patients with chronic liver disease and cancer. We report here a case presenting with spontaneous chylous ascites in cirrhosis of liver. It has been associated with poor prognosis. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 42-45 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6837